KOMUNIKASI DALAM KEPERAWATAN GIGI DAN KEPUASAN PASIEN DI KLINIK GIGI JURUSAN KEPERAWATAN GIGI POLTEKKES KEMENKES RI MEDAN (STUDI DESKRIPTIF) - Manta Rosma (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2017)
Communication in dental hygiene is the one that is consciously designed for patients’ recovery. In order to perform a good communication in dental hygiene, every nurse requires good knowledge and attitude. This is descriptive research with survey method which objective was to measure the patients’ satisfaction level at Dental Clinic of Dental Hygiene Department, Poltekkes Kemenkes RI (Polytehnic of Health, Minstry of Health of the Republic of Indonesia), Medan. The primary data were gained through questionnaires. The secondary data were obtained from the visit recording book of the patients at Dental Clinic of Dental Hygiene Department, Poltekkes Kemenkes RI Medan. The samples were 40 patients who were selected using purposive sampling technique. The result showed that 17 respondents (42,5%) were satisfied and 23 respondents (57,5%) were dissatisfied. It was concluded that the communication in dental hygiene is very essential. It is recommended that the quality of communication at the Dental Clinic of Dental Hygiene Department, Poltekkes Kemenkes RI Medan be improved , for example by developing students’ ability in communicating with patients and enhancing the adequate facilities in order that the optimal and good oral and dental health service can be achieved.